If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-p)/(8)=6+6p
We move all terms to the left:
(-p)/(8)-(6+6p)=0
We add all the numbers together, and all the variables
(-1p)/8-(6p+6)=0
We get rid of parentheses
(-1p)/8-6p-6=0
We multiply all the terms by the denominator
(-1p)-6p*8-6*8=0
We add all the numbers together, and all the variables
(-1p)-6p*8-48=0
Wy multiply elements
(-1p)-48p-48=0
We get rid of parentheses
-1p-48p-48=0
We add all the numbers together, and all the variables
-49p-48=0
We move all terms containing p to the left, all other terms to the right
-49p=48
p=48/-49
p=-48/49
| 6w^2=864 | | 1/2x+4=3x-2x | | F(x)=0.5x^2+|x|+3 | | 12x-12=11x | | x+1+x+1=0 | | 6.5x-5.25=9.75-3.5 | | x/2-4x/3=3 | | X/2+x/3=5x+2/6 | | 11/6=p+4/12 | | 5/6+1/6t=4/6 | | .5x+.66=11/3 | | 4x+3=31 | | m2=9/64 | | -5(2+1)=-2z+10 | | P(x)=75X-8X^3 | | 6-x-3=x-8 | | 2x-10=3x+6 | | 114=1/2h(10+9) | | 2y+4+4y=11-y | | 64-4x=8x-24 | | 2(x+2)=10x-8 | | 2x^2+2x-285=0 | | 0.80x+60=120 | | a/4-1=a/3+6 | | 2(x-1)^2+7=39 | | 6+9v=2(v–11) | | 13-x+5=2 | | 53x+64=52x-97 | | 4(x+2)=12x-28 | | n/3-1/2=7/6 | | 2/3x+3=2/5x-1 | | 2y’+3y=0 |